The Strategy for Use of “Zungenbrecher - Einfach Deutsch Lernen” in Learning German - Anavi, Wilma Prisca; Febriane, Dhania; Putri Kurnia, Amanda; Aprilianah, Jihaan (Nexus Publishing NXP, 2024)
In this era of globalization, there is an urgent need to learn foreign languages. Not only English, which is an international language, but also other foreign languages, including German. According to a Deutsche Welle news article with the topic